Transnationalism and Transculturalism in the History of Education - Roith, Christian; Sáez Castro, Luis Miguel; Sánchez Muñoz, Carlos (Historia y Memoria de la Educación, 2025)
The History of Education has undergone a profound methodological and conceptual transformation in recent decades, driven by the need to transcend national frameworks and explore the processes of circulation, interaction, and fusion of educational ideas, practices, and subjects across borders. This special issue of History and Memory of Education is dedicated to the topic of Transnationality and Transculturality in the History of Education during Modernity and the Contemporary Period. This special issue arises as a direct result of the 22nd Colloquium on the History of Education, held at the University of Almería from September 11 to 13, 2024. The Colloquium, organized by the Department of Theory and History of Education at the University of Almería, aimed to address a field of research that in recent years has begun to examine ideas, objects, practices, and explanatory strategies that transcend national borders.